Analisis Profitabilitas, Likuiditas dan Solvabilitas Terhadap Kinerja Keuangan Pada Perusahaan Food and Beverage yang terdaftar di BEI Tahun 2018-2020 - Deandra Naddienalifa; Triyono Adi Tristanto; Ahmad Nurdin Hasibuan; Harisman Harisman (Unversitas Prof. Dr. Moestopo (Beragama), 2021)
This research aims to determine the analysis of Profitability by proxy Return On Assets, Liquidity by proxy Current Ratio, Solvency with proxy Debt to Equity Ratio and Financial Performance by proxy Return On Equity. The data obtained are 14 companies for the period 2018-2020. The data analysis methods used were normality test, autocorrelation test, multicollinearity test, heteroscedasticity test and t test. The results showed that the Return On Assets variable had a significant and significant effect on Return On Equity. While the Current Ratio has no effect and is not significant on Return On Equity. And the Debt to Equity Ratio has a significant and significant effect on Return On Equity.